Understanding the Contemporary Character of Braamfontein Johannesburg: Towards a renewed understanding of urban renewal in cities in the South - Katz, Ivanna (Department of Environmental and Geographical Science, 2020)
Work on urban renewal internationally focuses on a vast range of topics, including gentrification, increased criminalization of poverty, rent-seeking behaviour, and neoliberal urbanism. These arguments tend to centre the interests and actions of certain actors, prioritize certain forces (such as economic ones), and thus tend to predict a particular set of outcomes. In adopting a southern urbanist epistemology, and Jennifer Robinson’s reimagined comparativism through a reconceptualized 'case’, this research shows how predominant assumptions regarding the drivers and outcomes (both social and physical) of urban renewal do not necessarily apply in the case of Braamfontein, an instance of urban renewal in Johannesburg, a post-apartheid city in the south. The findings examined here include policy narratives and empirical referents to culture-led strategies of urban renewal and ways in which they speak less to market-orientated objectives, and more to socio-political ones; how the findings in Braamfontein speak to literature on gentrification, studentification, and youthification, showing that urban renewal and gentrification are not the same processes, and that studentification does not necessarily lead to youthification or gentrification; how attempts to suppress informal trade have led to the proliferation of iterant strategies on the part of hawkers, and have in turn led to enhanced relationships between informal traders and the formal economy; and, finally, how the presence of communities self-identifying as foreign or gay are shown to be driven by forces other than those that the literature typically predicts.